A Comparative Case Study Analysis of Barriers and Facilitators to Implementing the Affordable Care Act's Balancing Incentive Program. (March 2022) - Beauregard, Lisa Kalimon; Miller, Edward Alan
The Affordable Care Act included the opportunity for states to increase spending on Medicaid home and community-based services (HCBS) for older adults and persons with disabilities through the Balancing Incentive Program (BIP). This study utilized comparative case studies to identify the factors that facilitated or impeded states' implementation of BIP. Findings indicate factors that facilitated the implementation of BIP were communication with the federal government and its contractor, merging BIP with existing HCBS programs, and enhanced federal revenue. On the other hand, the short duration of BIP, state procurement and contracting processes, and the need to incorporate feedback from non-governmental stakeholders and determining how to spend the enhanced revenue proved challenging for some states. This research suggests ways federal and state officials can implement new initiatives to achieve greater rebalancing of Medicaid long-term services and supports for older adults.